Diff erence and Identity: Two Paradigms of Patristic Philosophy - Gaginskii Aleksei (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
My main thesis looks as follows. Two fundamental paradigms were developed in Christian culture in the 4th с. AC. and largely determine philosophical and theological thought in East and West: 1) the identity paradigm, which became widespread in the West after Augustine, involves the identiﬁcation of essence and predicates in God; 2) the paradigm of diﬀerence, which became widespread in the East thanks to Cappadocian Fathers, involves fundamental diﬀerence between essence and predicates in God. These approaches are not only private theological opinions, but lie at the beginning of the two branches of the Christian metaphysics. I argue that identity paradigm is imperfect from theological and philosophical points of view, while the paradigm of diﬀerence has a rich philosophical and theological potential, however, it has not been studied suﬃ ciently.